Media Students' Approaches Towards the Use of Mobile Phones in Producing Short Films - Tnoh, Ahmad Mohammed (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify the attitudes of media students in Palestinian universities towards using mobile phones in producing short films, the advantages provided by it, and the prospects resulting from employing the mobile phone in producing short films. Methods: This study was based on a quantitative questionnaire tool. The sample included 170 students who demonstrated their success at eight media colleges in Palestine. They were randomly chosen based on the geographic distribution of universities with their various branches in the north, center, and south of the West Bank. Results: The results showed that the most important motivations for media students to use mobile phones were that it helps them to be self-reliant in producing short films and that it is easy to use due to its small size. One of the most significant implications of using mobile phones in producing short films is the increase in the production of self-story films and the simplification of the ideas addressed in the short film. Low lighting conditions in some locations and the lack of artificial lighting are considered the most important obstacles to its use in the production of short films by students. Conclusions: The percentage of media students using mobile phones to produce short films in Palestinian universities is high, especially with their expectation of witnessing an increase in smartphone devices and cameras, allowing an increasing number of users in film production.